2007
DOI: 10.1111/j.1572-0241.2007.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Breath Methane Production in IBS Correlates With the Severity of Constipation

Abstract: Methane on LBT is associated with constipation both subjectively and objectively. The degree of methane production on breath test appears related to the degree of constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 22 publications
7
144
2
11
Order By: Relevance
“…Elevated levels of fermentation intermediates in IBS stools might point to a disbalance of the gut environment and intestinal microbiota in this disease, leading to reduced metabolite cross-feeding among microbes and a resulting incomplete fermentation process. Because formate is utilized in the gut by methanogenic microbes, increased fecal formate is consistent with a lower methanogenic activity in the IBS-D lumen (Chatterjee et al, 2007). And as intestinal methane adversely affects gut transit time Fecal microbe-metabolite associations in health and IBS V Shankar et al (Ghoshal et al, 2011), lower methane production in IBS-D would facilitate faster gut transit resulting in a more frequent bowel movement.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated levels of fermentation intermediates in IBS stools might point to a disbalance of the gut environment and intestinal microbiota in this disease, leading to reduced metabolite cross-feeding among microbes and a resulting incomplete fermentation process. Because formate is utilized in the gut by methanogenic microbes, increased fecal formate is consistent with a lower methanogenic activity in the IBS-D lumen (Chatterjee et al, 2007). And as intestinal methane adversely affects gut transit time Fecal microbe-metabolite associations in health and IBS V Shankar et al (Ghoshal et al, 2011), lower methane production in IBS-D would facilitate faster gut transit resulting in a more frequent bowel movement.…”
Section: Discussionmentioning
confidence: 97%
“…Repeat breath samples were then obtained 15 minutes after lactulose ingestion, and levels of methane and hydrogen were analyzed using gas chromatography (Quintron instrument company, Milwawkee, WI). A positive methane breath test was defined as a breath methane level ≥3 parts per million (ppm) as previously published [20,23]. Of these subjects, 15 non-methane and 5 methane positive subjects were consented to undergo an oral glucose tolerance test (OGTT).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, breath methane has been associated with constipation: we found that subjects with IBS who have methane on breath test were almost universally constipated [20], and subsequent studies showed methane to be predictive of constipation among functional bowel disease patients [23] as well as in IBS and non-IBS subjects [24]. In a meta-analysis of 1277 IBS patients, we found that methane was associated with constipation, with a pooled OR=3.51 (CI=2.00-6.16) [25].…”
Section: Introductionmentioning
confidence: 99%
“…spp. is increased in IBD patients (Chatterjee et al, 2007, Blais Lecours et al, 2014. With all these factors considered it led me to hypothesise that the abundance and profile of the methanogenic community within CKD…”
Section: Discussionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is categorised by episodes of diarrhoea (IBS-D), constipation (IBS-C), or both (IBS-M), and breath methane measurement of IBS patients has been reported to be greater in IBS-C and lower or not detectable in IBS-D patients (Chatterjee et al, 2007). It has been demonstrated in animal and human models that methane can influence the intestinal motor function, with an abundance of methane resulting in a slow intestinal transit time as a result of augmented small bowel contractile activity (Pimentel et al, 2006).…”
Section: Interactions Between Methanogenic Archaea and The Human Hostmentioning
confidence: 99%